Evaluation of Childhood Traumas, Depressive Symptoms, and Dissociative Experiences in Tinnitus Cases - Mustafa Altıntaş; Deniz Sarlak; Erdinç Özturk; Osman Celbiş (Medeniyet Medical Journal)
Objective: Tinnitus is described as the perceived sound without any external stimulus and is a common problem, but its mechanism is not fully understood. This study aimed to evaluate childhood traumas and dissociative experiences, which may be predisposing factors in patients with tinnitus. Methods: The study included 90 voluntary patients (45 patients with tinnitus and 45 in the control group) aged older than 18 years who applied to the otorhinolaryngology clinic between November 2018 and February 2019 and were diagnosed with subjective tinnitus. A personal information form together with childhood trauma, hospital anxiety and depression, and dissociative experiences scales were used to assess the patients. Results: Of all participants, 55.60% were males, 28.90% were 20-30 years old, 71.10% were married, 40% were primary school graduates, and 68.90% were employed. In addition, 77.78% of patients did not visit a psychiatrist and 75.56% did not have any chronic diseases. The mean total score of Childhood Trauma Scale for the tinnitus group was 54.37±10.17, the mean total score of The Hospital Anxiety and Depression Scale for the tinnitus group in the depression subscale was 12.22±5.41 and in the anxiety subscale was 10.54±3.5, and Dissociative Experiences was 13.48±4.68. A positive significant relationship was found between the childhood traumas of the tinnitus cases in their depressive symptoms, and dissociative experiences (p<0.05). Conclusions: The study results found a positive relationship between the childhood traumas and dissociative experiences of tinnitus cases, which can be considered as predisposing factors in patients with tinnitus who should also be investigated for childhood trauma, and the treatment approach should be multidisciplinary.